2019
DOI: 10.1016/j.apsb.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing vitamin D for treatment of human malignancies via targeting tumor microenvironment

Abstract: Tumor cells along with a small proportion of cancer stem cells exist in a stromal microenvironment consisting of vasculature, cancer-associated fibroblasts, immune cells and extracellular components. Recent epidemiological and clinical studies strongly support that vitamin D supplementation is associated with reduced cancer risk and favorable prognosis. Experimental results suggest that vitamin D not only suppresses cancer cells, but also regulates tumor microenvironment to facilitate tumor repression. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 186 publications
(252 reference statements)
3
69
0
2
Order By: Relevance
“…These results show that 1,25(OH) 2 D 3 action extends to tumor stromal fibroblasts and that 1,25(OH) 2 D 3 is an important regulator of CAF differentiation. Together with other findings suggesting anti-inflammatory and anti-angiogenic effects of 1,25(OH) 2 D 3 at the level of immune and endothelial cells [ 122 ], they widen the prodifferentiation action of 1,25(OH) 2 D 3 to cells of the tumor microenvironment, which may have important consequences on cancer development.…”
Section: Effects Of 125(oh) 2 Dsupporting
confidence: 68%
“…These results show that 1,25(OH) 2 D 3 action extends to tumor stromal fibroblasts and that 1,25(OH) 2 D 3 is an important regulator of CAF differentiation. Together with other findings suggesting anti-inflammatory and anti-angiogenic effects of 1,25(OH) 2 D 3 at the level of immune and endothelial cells [ 122 ], they widen the prodifferentiation action of 1,25(OH) 2 D 3 to cells of the tumor microenvironment, which may have important consequences on cancer development.…”
Section: Effects Of 125(oh) 2 Dsupporting
confidence: 68%
“…The TME, which consists of resident fibroblasts, endothelial cells, pericytes, leukocytes, extracellular matrix, immune cells 17 , 18 , and the immune cells infiltrated in the solid tumor such as macrophages or neutrophils play a significant role in the metastasis of malignancy 19 , 20 , 21 , 22 . Therefore, we hypothesized that targeting a molecule that can regulate the tumor immune microenvironment along with anti-VEGFR2 may solve the problem of invasiveness and metastasis that is induced by VEGF/VEGFR2 inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that anti-angiogenic drugs can normalize tumor blood vessels within a certain time window, which can improve tumor blood flow perfusion and enhance chemotherapeutic drug delivery into tumors 27 , 41 . This may alter the microenvironment and metabolic state of cancer cells 42 , which makes them more sensitive to chemotherapy, radiotherapy or immunotherapy. In this study, we demonstrated that SMI can prune the microvessels and promote vascular maturation, which lead to improved vascular structure.…”
Section: Discussionmentioning
confidence: 99%